Connecting the progenitors, pre-explosion variability and giant outbursts of luminous blue variables with Gaia16cfr. Issue 4 (13th October 2017) - Kilpatrick, Charles D.; Foley, Ryan J.; Drout, Maria R.; Pan, Yen-Chen; Panther, Fiona H.; Coulter, David A.; Filippenko, Alexei V.; Marion, G. Howard; Piro, Anthony L.; Rest, Armin; Seitenzahl, Ivo R.; Strampelli, Giovanni; et al.
Abstract: We present multi-epoch, multicolour pre-outburst photometry and post-outburst light curves and spectra of the luminous blue variable (LBV) outburst Gaia16cfr discovered by the Gaia satellite on 2016 December 1 ut . We detect Gaia16cfr in 13 epochs of Hubble Space Telescope imaging spanning phases of 10 yr to 8 months before the outburst and in Spitzer Space Telescope imaging 13 yr before outburst. Pre-outburst optical photometry is consistent with an 18 M⊙ F8 I star, although the star was likely reddened and closer to 30 M⊙ . The pre-outburst source exhibited a significant near-infrared excess consistent with a 120 au shell with 4 × 10 −6  M⊙ of dust. We infer that the source was enshrouded by an optically thick and compact shell of circumstellar material from an LBV wind, which formed a pseudo-photosphere consistent with S Dor-like variables in their 'maximum' phase. Within a year of outburst, the source was highly variable on 10–30  d time-scales. The outburst light curve closely matches that of the 2012 outburst of SN 2009ip, although the observed velocities are significantly slower than in that event. In H α, the outburst had an excess of blueshifted emission at late times centred around −1500 km s −1, similar to that of double-peaked Type IIn supernovae and the LBV outburst SN 2015bh. From the pre-outburst and post-outburst photometry, we infer that the outburst ejecta are evolving into a dense, highly structured circumstellar environment from precursor outbursts within years of the 2016 December event.